2015
DOI: 10.1021/acs.macromol.5b00452
|View full text |Cite
|
Sign up to set email alerts
|

PTFE Tribology and the Role of Mechanochemistry in the Development of Protective Surface Films

Abstract: The wear and friction behavior of ultralow wear polytetrafluoroethylene (PTFE)/α-alumina composites first described by Burris and Sawyer in 2006 has been heavily studied, but the mechanisms responsible for the 4 orders of magnitude improvement in wear over unfilled PTFE are still not fully understood. It has been shown that the formation of a polymeric transfer film is crucial to achieving ultralow wear on a metal countersurface. However, the detailed chemical mechanism of transfer film formation and its role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
199
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 251 publications
(227 citation statements)
references
References 59 publications
24
199
2
2
Order By: Relevance
“…They found that running film hardness and modulus increase with increased sliding distance and decreased wear rates [24]. They suggested that changes in mechanical properties reflect filler accumulation and tribochemical degradation of PTFE, which is consistent with their more recent papers on the evolution of interface chemistry [27,29] and particle enrichment [30]. Ye [42] conducted similar measurements on transfer films from the same system.…”
Section: Mechanical Properties Of the Transfer Filmsupporting
confidence: 66%
See 4 more Smart Citations
“…They found that running film hardness and modulus increase with increased sliding distance and decreased wear rates [24]. They suggested that changes in mechanical properties reflect filler accumulation and tribochemical degradation of PTFE, which is consistent with their more recent papers on the evolution of interface chemistry [27,29] and particle enrichment [30]. Ye [42] conducted similar measurements on transfer films from the same system.…”
Section: Mechanical Properties Of the Transfer Filmsupporting
confidence: 66%
“…In addition to producing thinner and more uniform transfer films, low-wear alumina-PTFE transfer films are obviously discolored [13,18,20,[23][24][25][26][27]29,31,32,[37][38][39], which suggests chemical reactions had taken place and possibly enhanced adhesion of the transfer film. In 2013, Ye and Burris used optical microscopy to determine the degree to which transfer films persist during sliding [20].…”
Section: The Effects Of Filler Characteristics On Transfer Films and mentioning
confidence: 99%
See 3 more Smart Citations